Um estudo sobre índices de campos de vetores - Bacelar, Leandro de Jesus Nascimento (Universidade Federal de São Carlos, 2023)
One of the main goals of this project is to study the index of vector fields in compact surfaces and present the Poincar´e-Hopf Theorem, remarking that such a result connects topological elements to geometric objects.
A study on indices of vector fields
Keywords: Topologia diferencial; Índice de campos de vetores; Superfícies diferenciáveis; Differential topology; Vector field index; Differentiable surfaces; CIENCIAS EXATAS E DA TERRA::MATEMATICA